A controller for brushless direct current electric motors. Part 2. Software - Syroka, Zenon (Technical Sciences, 2020)
A universal controller for brushless direct current (BLDC) motors was designed in the presented article. The system is controlled from the user console where operating parameters are set by the user. Signals are transmitted by cables to microcontrollers which control and monitor electric motors. Microprocessors communicate via a data bus. The controller contains the user console module and the motor control module. The user console module generates commands, and motors are controlled and monitored by the control module. Motor control modules operate independently, and each brushless motor has a dedicated control module. Brushless motors can be controlled in bipolar or unipolar mode. The control method is selected by the operator. The user console and motor controllers communicate via the I²C bus.